Evaluating the Measures to Promote Sustainable Transport Infrastructure: A Case of City of Johannesburg, South Africa - Ntebo Ngcobo; Opeoluwa Akinradewo; Phindile Mokoena (Journal of Engineering)
The transition towards sustainable transport infrastructure requires comprehensive measures that address the complex interplay between economic, environmental and social factors. The surge in road traffic levels poses a primary threat to metropolitan areas, leading to congestion and reduced feasibility of public transportation, ultimately impacting accessibility. Addressing the environmental impact of transportation, reducing greenhouse gas emissions and implementing green cover cultivation and electric transport infrastructure policies are crucial steps in achieving sustainable transportation in urban areas. Therefore, the study aims to evaluate measures to promote sustainable transport infrastructure in Johannesburg. The paper adopted a quantitative research method with the targeted respondents as people responsible for the delivery and construction of the road infrastructure. The questionnaires were also in the form of closed-ended multiple-choice questions. The respondents’ responses were analysed using the mean item score (MIS) and factor analysis. The findings revealed that the primary measures to improve the sustainability of existing transportation infrastructure are promoting green infrastructure construction, enhancing transportation facilities to attract more public transportation users, such as safe taxi ranks and embracing traffic management measures. The study concluded by emphasising the increasing recognition of green infrastructure as a holistic strategy to address environmental challenges and improve transportation efficiency within current urban transport systems. It is therefore recommended that cities prioritise the integration of green infrastructure, including eco-friendly transit systems, renewable energy sources and eco-corridors, into urban transport systems to address environmental challenges and improve transportation efficiency.